2022
DOI: 10.20473/vol9iss20223pp362-378
|View full text |Cite
|
Sign up to set email alerts
|

Penilaian Dampak Zakat, Infak, Sedekah Terhadap Kemiskinan Spiritual Dan Material Penerima Manfaat Laznas LMI: Pendekatan CIBEST

Abstract: ABSTRAK Kemisikinan merupakan suatu permasalahan yang harus ditemukan cara mengentaskannya. Islam agama yang sempurna telah memberikan solusi melalui instrument zakat, infak, dan sedekah. Tujuan dari penelitian ini adalah untuk menilai dampak zakat, infak, sedekah di LAZNAS LMI (Lembaga Manajemen Infaq) dengan Pendekatan CIBEST. Metode penelitian yang digunakan adalah kuantitatif dengan uji beda antara kondisi material dan spiritual mustahik sebelum dibantu dengan setelah disalurkan dana ZIS. Hasil analisis da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…It can be concluded that there is a difference between the results after and before being assisted. The results align with the studies conducted by Efendi and Fathurrohman (2021); Jaenudin and Hamdan (2022). They found differences in material welfare conditions before and after being assisted by ZIS funds.…”
Section: Wilcoxon Signed Rank Test and Hypothesis Testingsupporting
confidence: 90%
See 1 more Smart Citation
“…It can be concluded that there is a difference between the results after and before being assisted. The results align with the studies conducted by Efendi and Fathurrohman (2021); Jaenudin and Hamdan (2022). They found differences in material welfare conditions before and after being assisted by ZIS funds.…”
Section: Wilcoxon Signed Rank Test and Hypothesis Testingsupporting
confidence: 90%
“…Ali et al (2013) stated that the distribution of zakat has a significant and positive effect on increasing income distribution for the poor. Jaenudin and Hamdan (2022) found that ZIS can increase material welfare as measured by increasing income to get out of poverty. Nurhasanah (2020) showed that the utilization of productive zakat funds has a significant influence on the level of income of mustahik at BAZNAS Palopo City.…”
Section: Previous Study and Hypothesismentioning
confidence: 99%
“…Data from the Central Statistics Agency in 2022 indicated that the number of poor people in Indonesia as of September 2021 was 26.50 million, a decrease of 1.04 million from March 2021. To evaluate the performance of zakat management, BAZNAS has been measuring the impact of zakat on the welfare of mustahiks (zakat recipients) since 2016, using the Zakat Impact Assessment instrument(Widiawati et al, 2018;Jaenudin & Hamdan, 2022; A. T. G. N Azizah et al, 2023)…”
mentioning
confidence: 99%